2023
DOI: 10.1371/journal.pone.0277901
|View full text |Cite
|
Sign up to set email alerts
|

Peak match acceleration demands differentiate between elite youth and professional football players

Abstract: Youth footballers need to be developed to meet the technical, tactical, and physical demands of professional level competition, ensuring that the transition between competition levels is successful. To quantify the physical demands, peak match intensities have been measured across football competition tiers, with team formations and tactical approaches shown to influence these physical demands. To date, no research has directly compared the physical demands of elite youth and professional footballers from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
2
5
0
1
Order By: Relevance
“…These results are partially analogous to those obtained in previous research carried out on elite professional and youth players, which concluded that both Ac and Dec tended to decrease gradually between periods, but also within each period, due to the effect of accumulated physical and mental fatigue [2,14,27,[37][38][39]. The underlying mechanism explaining this difference in Ac/Dec behavior is not clear.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…These results are partially analogous to those obtained in previous research carried out on elite professional and youth players, which concluded that both Ac and Dec tended to decrease gradually between periods, but also within each period, due to the effect of accumulated physical and mental fatigue [2,14,27,[37][38][39]. The underlying mechanism explaining this difference in Ac/Dec behavior is not clear.…”
Section: Discussionsupporting
confidence: 86%
“…They typically sprint 600-1200 m at high speed and perform 60 to 100 accelerations. Similar figures are observed for elite youth players [4,14]. The common practice of evaluating professional football performance using the high-speed running threshold (19.8-25.1 km•h −1 ) overlooks the energy expenditure associated with Ac/Dec, thus underestimating a player's workload [15].…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations